Towards a unified conception of nature. Conciderations on the basis of Popper’s conception of three worlds - Ogrodnik, Bogdan (Folia Philosophica, 2006)
The article discusses metaphysical implications of Popper's conception of three worlds, conception of language and conception of evolution. It also shows that these conceptions can be written into a wider perspective referring to metaphysics of A.N. Whitehead.